Association of common genetic variants related to atrial fibrillation and the risk of ventricular fibrillation in the setting of first ST-elevation myocardial infarction - Reza Jabbari; Javad Jabbari; Charlotte Glinge; Bjarke Risgaard; Stefan Sattler; Bo Gregers Winkel; Christian Juhl Terkelsen; Hans-Henrik Tilsted; Lisette Okkels Jensen; Mikkel Hougaard; Stig Haunsø; Thomas Engstrøm; et al. (BMC, 2017)
Abstract Background Cohort studies have revealed an increased risk for ventricular fibrillation (VF) and sudden cardiac death (SCD) in patients with atrial fibrillation (AF). In this study, we hypothesized that single nucleotide polymorphisms (SNP) previously associated with AF may be associated with the risk of VF caused by first ST-segment elevation myocardial infarction (STEMI). Methods We investigated association of 24 AF-associated SNPs with VF in the prospectively assembled case-control study among first STEMI-patients of Danish ancestry. Results We included 257 cases (STEMI with VF) and 537 controls (STEMI without VF). The median age at index infarction was 60 years for the cases and 61 years for the controls (p = 0.100). Compared to the control group, the case group was more likely to be male (86% vs. 75%, p = 0.001), have a history of AF (7% vs. 2%, p = 0.006) or hypercholesterolemia (39% vs. 31%, p = 0.023), and a family history of sudden death (40% vs. 25%, p < 0.001). All 24 selected SNPs have previously been associated with AF. None of the 24 SNPs were associated with the risk of VF after adjustment for age and sex under additive genetic model of inheritance in the logistic regression model. Conclusion In this study, we found that the 24 AF-associated SNPs may not be involved in increasing the risk of VF. Larger VF cohorts and use of new next generation sequencing and epigenetic may in future identify additional AF and VF risk loci and improve our understanding of genetic pathways behind the two arrhythmias.